Enhancement of Photophysical and Photosensitizing properties of Flavin Adenine Dinucleotide by Mutagenesis of the C-terminal extension of a bacterial Flavodoxin Reductase - Valle, Lorena (2015)
The role of the mobile C-terminal extension present in Rhodobacter capsulatus ferredoxin–NADP(H) reductase (RcFPR) was evaluated using steady-state and dynamic spectroscopies for both intrinsic Trp and FAD in a series of mutants in the absence of NADP(H). Deletion of the six C-terminal amino acids beyond Ala266 was combined with the replacement A266Y to emulate the structure of plastidic reductases. Our results show that these modifications of the wild-type RcFPR produce subtle global conformational changes, but strongly reduce the local rigidity of the FAD-binding pocket, exposing the isoalloxazine ring to the solvent. Thus, the ultrafast charge-transfer quenching of 1 FAD* by the conserved Tyr66 residue was absent in the mutant series, producing enhancement of the excited singletand triplet-state properties of FAD. This work highlights the delicate balance of the specific interactions between FAD and the surrounding amino acids, and how the functionality and/or photostability of redox flavoproteins can be modified.